Strategies to compare clinical antitherapeutic antibody data when changing assay platforms: a case study. (August 2015) - Qiu, Zhihua Julia; Ying, Yong; Lewin-Koh, Sock-Cheng; Coleman, Daniel; Brignoli, Suzanne; Hendricks, Robert; Siguenza, Patricia; Quarmby, Valerie; Fischer, Saloumeh K; Song, An
Zhihua Julia Qiu has over 20 years post PhD experience in academic institutes, pharmaceutical industry and biotechnology startup settings; focused on novel therapeutics discovery and development and diagnostic tools. She is currently a Scientist in the Bioanalytical Sciences department at Genentech; responsible for developing, evaluating and implementing Bioanalytical strategy to support protein therapeutics development. That includes assay development and validation to evaluate PK, antitherapeutic antibodies as well as biomarkers in both nonclinical and clinical studies for Immunology and Oncology indications. In addition, she has led the evaluation of multiple novel technology platforms and transitioning assay platform to enable continuous support for the development of protein therapeutics and antibody–drug conjugates. Due to the discontinuation of the BioVeris electrochemiluminescence assay (ECLA) platform, an alternative antitherapeutic antibody (ATA) platform had to be identified to continued support the development of a monoclonal antibody therapeutic (rhuMAb A). A sample set including both positive and negative responses from a clinical study of rhuMAb A was selected and analyzed for the comparison of ATA data from ECLA and a newly developed bridging DIG ELISA. A comparison of data from ECLA and ELISA was performed. The results demonstrate that there was 97.4% concordance between ATA study sample results from the two assay platforms. The results show that replacing the ATA assay platform from ECLA to DIG ELISA would not have a significant impact on the immunogenicity assessment of rhuMAb A.